Vascular response to percutaneous coronary intervention with biodegradable-polymer vs. new-generation durable-polymer drug-eluting stents: a meta-analysis of optical coherence tomography imaging trials. (2nd January 2018) - Cassese, Salvatore; Xhepa, Erion; Ndrepepa, Gjin; Kufner, Sebastian; Colleran, Roisin; Giacoppo, Daniele; Koppara, Tobias; Mankerious, Nader; Byrne, Robert A; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Fusaro, Massimiliano; et al.
Abstract: Aims: Whether biodegradable-polymer drug-eluting stents (BP-DES) induce a vascular response at follow-up more favourable than that of new-generation durable-polymer drug-eluting stents (DP-DES) remains controversial. We sought to evaluate the vascular response to percutaneous coronary intervention (PCI) with BP-DES vs. new-generation DP-DES as assessed by optical coherence tomography (OCT) imaging at follow-up. Methods and results: We undertook a meta-analysis of aggregate data by searching electronic scientific databases for investigations of PCI-patients receiving BP-DES vs. new-generation DP-DES and OCT imaging at follow-up. The primary outcome was neointima hyperplasia (NIH) thickness. The co-primary outcome was the incidence of lesions with uncovered struts. The main secondary outcome was the incidence of lesions with malapposed struts. Among 10 trials, a total of 544 PCI-patients were assigned to BP-DES ( n = 282) or new-generation DP-DES ( n = 262). Of these, 447 participants with 480 treated lesions had analysable OCT imaging at a weighted median follow-up of 7 months. Lesions treated with BP-DES vs. new-generation DP-DES showed comparable NIH thickness [weighted mean difference 95% confidence intervals (CI) = −11.37 (−29.25, 6.52); P = 0.21]. However, thick-struts (>100 μm) BP-DES showed less NIH thickness as compared to new-generation DP-DES [−20.39 (−33.83, −6.95); P = 0.003]. BP-DES vs. new-generation DP-DES showed a higher risk for uncovered struts [odds ratio 95% CI = 3.50 (1.69–7.26); P = 0.0008] and a trend towards higher risk for malapposed struts [2.01 (0.98–4.12); P = 0.06]. Conclusion: In PCI-patients with available OCT imaging at follow-up, BP-DES with thicker backbones delay vascular response as compared with new-generation DP-DES.